Exploiting Drama for Children in EFL Teaching to Promote Creativity, Confidence, and Motivation - Ahmad Ridho Rojabi; Ali Mustofa (Universitas Bengkulu, 2021)
Drama is a powerful tool for actively engaging children in the English learning process. By creating meaningful contexts, drama techniques help them develop their integrated linguistic competence. This research aims to explore how drama impacts the students’ confidence, creativity, and motivation to learn. This research used a literature review by selecting appropriate journal articles regarding drama in EFL teaching. The findings revealed that drama is beneficial in increasing students' confidence, creativity, and motivation to learn. Further research is recommended to exploit drama for children as it boosts the learners’ enthusiasm to learn English effectively.